Interfacial tension at the interface of a system of molten oxide and molten steel - Rosypalová, Silvie (Materiali in tehnologije, 2014)
This paper is focused on a study of the interfacial tension between selected oxide and metal phases. The experimental research on the interfacial tension was performed in a horizontal resistive graphite Tamman furnace using an original method of measuring. This method consists of fixing both liquid phases in a horizontal position using a mandrel made of tungsten wire in a corundum cover. In this work the influence of the carbon content in the steel on the interfacial tension was studied. For this purpose a steel with 0.411 % of mass fraction of carbon and a steel with 2.64 % of carbon were used. Because of the wide variety of oxide systems used in industry, a characteristic system of casting powder was chosen for this study. This system contains dominant components, i.e., SiO2, CaO, Al2O3 and MgO, as well as a range of attendant mixtures, e.g., Fe2O3, TiO2 and Na2O. Simultaneously, the influence of SiO2 on the temperature dependence of the interfacial tension was observed. For this reason a concentration series with gradual additions of SiO2 was created. It was found that an increasing content of carbon in the steel significantly decreases the interfacial tension between the oxide system and the steel. The interfacial tension was found to decrease slightly with an increase in the content of SiO2 in the oxide system.
Keywords: jeklo; steel; livni prašek; casting powder; interfacial tension; medfazna napetost